ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN BEROBAT DI PUSKESMAS DESA PASIR UTAMA - andari, efi; 'Aini, Yulfita; -, Asrori (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This research was conducted to analyze the effect of service quality to satisfaction of patients treated at the healthy center in Desa Pasir utama. The samples in this research are 44 respondents. There were methods of sampling used the technique Accidentals also. The method analysis was quantitative analysis used validity test, reliability test, simple linear regression analysis, the correlation coefficient, coefficient of determination, and hypothesis testing. Used simple linear regression analysis concluded that service quality effect on patient satisfaction, it can be seen from the results of the regression equation with the result Y = 4,421+ 0,589XX, value indicates that the X or the service quality effect on customer satisfaction by 0.589 or 58.9%. Based on the calculation of correlation coefficients obtained results sig (2-tailed) of 0.058 means that the relationships between the two variables are low. The coefficient of determination shows the influence of variable X to variable Y is strong. Hypothesis test figures obtained significance of 0.000. It means that there were influenced quality of service to the satisfaction of the patient, because 0,000 <0.05 it means the value of regression is feasible or correct. It is recommended to the chairman of the health center in Desa Pasir Utama to be more concerned about the quality of services provided by employees of health centers so that patients get satisfaction in accordance with what they expect, and the need for modern facilities in order to hold a health center can be trusted by the local community.